Pengaruh Infrastruktur Jalan, Ekspor, Wisatawan, dan Angka Harapan Hidup terhadap Pertumbuhan Ekonomi di Indonesia Tahun 2021-2025 - Nashwa Nareswari Putri; Naura Ajeng Haryanto; Kamelia Aji Aprilina; Nadia Khoirunnisa; Salsabilah Pakita; Fitri Amalia (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to analyze the effect of road infrastructure, non-oil and gas exports, tourist arrivals, and Life Expectancy Rate (AHH) on regional economic growth (GRDP) in 33 Indonesian provinces for the 2021–2025 period. Using secondary data from BPS and the Ministry of Trade, the model was estimated via panel data regression with an Unbalanced Panel approach (162 observations) using the Random Effect Model (REM). The partial results show that AHH, road length, and tourist arrivals have a positive and significant effect on regional GRDP, acting as the main drivers of the regional economy. Conversely, non-oil and gas exports exert a significant negative effect,  indicating structural weaknesses due to dependence on primary commodities without strong downstreaming. Therefore, future policies must focus on sustainable land connectivity, human capital improvement, and accelerating regional export downstreaming strategies.